Towards a synthesis of the biodiversity of freshwater Protozoa, Rotifera, Cladocera, and Copepoda in Brazil - Elmoor-Loureiro, L. M.A.; Sousa, F. D.R.; Oliveira, F. R.; Joko, C. Y.; Perbiche-Neves, G.; da Silva, A. C.S.; Silva, A. J.; Ghidini, A. R.; Meira, B. R.; Aggio, C. E.G.; Morais-Junior, C. S.; Eskinazi-Sant'Anna, E. M.; et al. (Elsevier, 2022)
Although Brazil is considered a megadiverse country, its rich freshwater biodiversity is still poorly known. A general overview of to-date knowledge on Protozoa, Rotifera, Cladocera, and Copepoda species and distribution in Brazilian Hydrographic Regions is presented here, based on literature data since the 1890s. Ecological studies provided most of the occurrence records. The results show high richness for all studied biological groups and unequal distribution of the occurrence records, which are substantially influenced by research groups’ location. The data also revealed that Brazilian zooplankton biodiversity still needs to be better studied, taxonomically, although from the beginning of the last century until 1980 these kinds of studies were predominant.
Keywords: Aquatic biology; Center of studies; Ecology; Neotropical; South America; Taxonomy; Trends